Esthetic perception of the smile according to gingival exposure in university students in Lima, Peru, 2020 - Abadíe Miranda, Mery Angela (2021)
Objective: To determine the esthetic perception of the smile according to gingival exposure in undergraduate university students of dentistry and other degrees of different ages and sex in Lima, Peru 2020, and descriptively evaluate the main variables such as age and sex. Methodology: A woman's smile was photographed following esthetic parameters, digitally modifying gingival exposure and obtaining six digital images. The images were rated by 512 students of dentistry and other degrees by means of a virtual survey using the Visual Analog Scale (values 0 to 10). Results: The students perceived the 0.5 mm gingival exposure smile as more attractive and the 2.5 mm gingival exposure smile as unattractive. According to age, students aged 18 to 23 years perceived the 0.5 mm gingival exposure smile as more attractive and the 2.5 mm gingival exposure smile as less attractive, while students aged 24 to 29 years perceived the 1 mm gingival exposure smile as more attractive and the 2 mm gingival exposure smile as unattractive. According to gender, both found the 0.5 mm gingival exposure smile more attractive and the 2.5mm gingival exposure smile unattractive. Conclusions: University students of dentistry and other degrees had the same perception of the smile in relation to gingival exposure, with a smile of 0.5 mm gingival exposure being considered attractive and the 2.5 mm smile unattractive. Younger students considered the smile with 0.5 mm gingival exposure more pleasant. Students of both sexes had the same esthetic perception of the smile.